Wolfgang Iser, Lo spettro dell'interpretazione (ENTHYMEMA, 2009)
We propose here the translation of two chapters from The Range of Interpretation by Wolfgang Iser, in which the German theorist provides an analysis of interpretation, with specific attention to the three operational modes of the hermeneutic circle, of the recursive loop and of the traveling differential in a perspective meant to highlight the role of interpretation as anthropological device, through an increasingly pregnant constructivist disposition leading to, in the end, to a series of ethical conclusions.